Digital Cultural Adjustment Pada Pondok Pesantren (Kajian Fenomenologis atas Pesantren Annuqayah Sumenep dan Tebuireng Jombang) - Faizatin (JSP: Jurnal Studi Pesantren, 2023)
This research is intended to find out the adaptation efforts of Pesantren Annuqayah and Tebuireng to digital culture, especially the process and form of adjustment to the advancement of digital technology which is currently an attribute of digital native santri. This research will answer three basic questions: First, what is the character of digital native santri in pesantren Annuqayah and Tebuireng, as connoisseurs of digital products? Second, how do they respond to the presence of digital native santri and the digital culture that enters the pesantren world? Third, what is the level of adaptation carried out by both pesantren as a barometer of their abilities? The analysis of this paper will utilize a theory developed by researcher called U-Cross Cultural Adjustment. This theory is a combination of three theories, technological determinism theory by Marshall McLuhan, integrative communication theory by Young Yun Kim, and acculturation theory by John W. Berry. This type of research is qualitative using a phenomenological approach to understand the events of the digital revolution in digital native santri and the decisions taken by pesantren Annuqayah and Tebuireng to respond to the situation in the form of descriptive analysis. In the end, it was concluded that there was an adaptation process of both pesantren to digital culture in several sectors, including the adaptation process in management, education management and social networking, although still it takes some different level of adjustment. This is due to the different culture shock between the two pesantren so that in the process some are slower and some are faster. In addition, human resources and the availability of pesantren facilities in the field of digitalisation also affect the level of adaptation.